Local and Global Framework of Early Cinema in Lithuania: Vilnius Cinemas, Programme Formats and Audience - Kaminskaitė-Jančorienė, Lina; Paškauskas, Juozapas (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The paper focuses on film culture in Lithuania by analysing the film programme advertisements in periodicals from the early cinema scene – 1907–1913. In the article, we present the specificities of the programmes of the key cinemas operating in Vilnius at that time, with reference to the programme composition by film type, genre, and the nature of film communication. A thorough analysis has allowed us to gain a clearer picture of film culture in the city, film circulation, and the communication strategies used by movie theatres to attract the audience. The analysis of this period enables a comparison of local early cinema processes in Lithuania with the global ones.